Germline Proliferation Is Regulated by Somatic Endocytic Genes via JNK and BMP Signaling in Drosophila. Issue 1 (1st May 2017) - Tang, Yaning; Geng, Qing; Chen, Di; Zhao, Shaowei; Liu, Xian; Wang, Zhaohui
Abstract: Signals derived from the microenvironment contribute greatly to tumorigenesis . The underlying mechanism requires thorough investigation. Here, we use Drosophila testis as a model system to address this question, taking the advantage of the ease to distinguish germline and somatic cells and to track the cell numbers. In an EMS mutagenesis screen, we identified Rab5, a key factor in endocytosis, for its nonautonomous role in germline proliferation. The disruption of Rab5 in somatic cyst cells, which escort the development of germline lineage, induced the overproliferation of underdifferentiated but genetically wild-type germ cells. We demonstrated that this nonautonomous effect was mediated by the transcriptional activation of Dpp [the fly homolog of bone morphogenetic protein (BMP)] by examining the Dpp-reporter expression and knocking down Dpp to block germline overgrowth. Consistently, the protein levels of Bam, the germline prodifferentiation factor normally accumulated in the absence of BMP/Dpp signaling, decreased in the overproliferating germ cells. Further, we discovered that the JNK signaling pathway operated between Rab5 and Dpp, because simultaneously inhibiting the JNK pathway and Rab5 in cyst cells prevented both dpp transcription and germline tumor growth. Additionally, we found that multiple endocytic genes, such as avl, TSG101, Vps25, or Cdc42, were required in the somatic cyst cells to restrict germline amplification. These findings indicate that when the endocytic state of the surrounding cells is impaired, genetically wild-type germ cells overgrow. This nonautonomous model of tumorigenesis provides a simple system to dissect the relation between tumor and its niche.